Implication of Nature Imageries in Puniyani’s Tangsing - Wagle, Anupa (JODEM: Journal of Language and Literature, 2023)
An anthology of Nepali Eco-poetry, Tangsing by Raja Puniyani includes nature imageries to focus its eco-theme in most of its poems. The two sections of this anthology as Eco-solo and Eco-chorus contain poems and poems in series respectively. So, the article investigates the nature imageries used in these poems and their connection with eco-theme in all the poems. The article analyses what imageries are used and how they directly and indirectly highlight to the human encroachment into nature and its consequences in future. To address these objectives, ecocritical theory, mainly the idea of Rachel Carson is used. Rachel Carson brings up the idea that how humans past activities leads them towards disastrous future related to nature and ecosystem of the earth. The significance of this study is to contribute to the reader to see the anthology seriously as a message to all human beings to save the earth and its ecosystem. The paper concludes that Tangsing is full of powerful nature imageries containing the eco-theme in almost all the poems in it. It paved the way towards eco-awareness through Nepali literature to address contemporary environmental issues faced by the world.